Litterarvm dvlces frvctvs : studies in early medieval latin culture in honour of Michael W. Herren for his 80th birthday - Bruce, Scott G.; Herren, Michael W. (Instrumenta patristica et mediaevalia, ISSN 1379-9878, 2021)
Litterarum dulces fructus' presents studies about medieval languages and literature in northern Europe in late antiquity and the Middle Ages. Drawing inspiration from the scholarship of Professor Michael Herren (founding editor of 'The Journal of Medieval Latin'), this florilegium of studies advances our understanding of the dynamics of Latin and vernacular literature and learning in the early medieval world. Taken together, the papers gathered in this volume cast light on authors, poets, glossators, and compilers at work as they grappled with linguistic and literary ambitions and challenges, while negotiating their use of ancient authorities to address contemporary concerns.
Keywords: Herren, Michael W., : 1940-; Middle Ages; Europe--History--476-1492; Latin language; Latin; Medeltiden